# The author uses the word "immediacy" (line 39) most likely in order to express

ChantraS on November 21, 2017

Transitive Property Slide - C exists

You stated that P: C exists C: D exists C: E exists We are not sure about B or A. But is the following correct N/S logic? P: not C -> not B C: not B -> not A C: not C -> not A

Replies

Mehran on November 21, 2017

@Chantra not sure I am understanding your question here.

ChantraS on November 21, 2017

If we negate C, is the contrapositve in the other direction (to B&A) correct?

Mehran on November 24, 2017

@ChantraS yes that would be correct.

P1: A ==> B
not B ==> not A

P2: B ==> C
not C ==> not B

We can combined these two using the transitive chain as follows:

A ==> B ==> C
not C ==> not B ==> not A

Hope that helps! Please let us know if you have any other questions.

tyler.channell7@gmail.com on September 30, 2018

I had a question. I feel like I am lost with the homework.

With Transitive Property, it doesn't have to be:

A=>B
B=>C
Therefore, A=>C

I can be:
not A=>B
B=>C
Therefore, not A=>C

Correct? Or am I just totally missing transitive property?

tyler.channell7@gmail.com on September 30, 2018

I also have another question on the homework.

I was going through the flash cards and I was wondering if there has to be a correct order to how transitive property works.

For example,

For the missing premise flash card it states:

P:D => A
P:C = A
P:
C: not X => A

The missing conclusion that I arrived at was:
not D => X (or Contrapositive: not X => D)

not C => X

Thanks.

Skylar on January 26, 2020

@tyler.channell7@gmail.com,

That is correct.

If we are given...:
P: not A -> B
not B -> A
P: B -> C
not C -> not B

...we can validly conclude:
not C -> not B -> A, or simplified: not C -> A
not A -> B -> C, or simplified: A -> not C

Therefore, the way the transitive property works remains the same regardless of what the variables are.

Skylar on January 26, 2020

@tyler.channell7@gmail.com,

Your answer is an equally valid possibility (assuming you meant to write the second given premise as "C->A" rather than "C=A").

We know
P: D -> A
not A -> not D
P: C -> A
not A -> not C
P: ?
C: not X -> A
not A -> X